Consequences of platforms' remuneration models for digital content: initial evidence and a research agenda for streaming services - Janek Meyn; Michael Kandziora; Sönke Albers; Michel Clement (Journal of the Academy of Marketing Science, 2022)
Nowadays, platforms in many industries offer content for a (monthly) flat rate (e.g., music streaming). While flat rates are efficient in reducing transaction costs for administering customers, platforms' rules for remunerating content right holders are crucial for royalty allocation and, as a result, heavily discussed in several industries. The music industry's business practices could be on the verge of their next disruption. There is an ongoing heated debate with respect to how the income of flat rates through streaming services should be allocated to right holders (labels and artists). This research investigates aspects of the supply and demand side effects as well as the resulting monetary consequences of changing the currently applied proportional-to-usage remuneration policy (pro rata) to a user-centric policy. Using individual-level data from 3,326 participants and data from Spotify's API, we empirically quantify the monetary consequences of this change for the music industry. Depending on the remuneration system, we find a substantial reallocation of nearly 170 million exteuro per year at Spotify. We discuss demand and supply-side consequences that may change the way music is currently produced and consumed. We conclude with a research agenda on the impact of business conventions for users, platforms, and artists in the music streaming industry.
Keywords: 330; Aggregators; Platforms; Remuneration policies; Music streaming industry